Associations between social vulnerabilities and dietary patterns in European children: the Identification and prevention of Dietary- and lifestyle-induced health EFfects In Children and infantS (IDEFICS) study. Issue 7 (26th September 2016) - Iguacel, Isabel; Fernández-Alvira, Juan M.; Bammann, Karin; De Clercq, Bart; Eiben, Gabriele; Gwozdz, Wencke; Molnar, Dénes; Pala, Valeria; Papoutsou, Stalo; Russo, Paola; Veidebaum, Toomas; Wolters, Maike; et al.
Abstract: Socio-economic inequalities in childhood can determine dietary patterns, and therefore future health. This study aimed to explore associations between social vulnerabilities and dietary patterns assessed at two time points, and to investigate the association between accumulation of vulnerabilities and dietary patterns. A total of 9301 children aged 2–9 years participated at baseline and 2-year follow-up examinations of the Identification and prevention of Dietary- and lifestyle-induced health EFfects In Children and infantS study. In all, three dietary patterns were identified at baseline and follow-up by applying the K-means clustering algorithm based on a higher frequency of consumption of snacks and fast food (processed), sweet foods and drinks (sweet), and fruits and vegetables (healthy). Vulnerable groups were defined at baseline as follows: children whose parents lacked a social network, children from single-parent families, children of migrant origin and children with unemployed parents. Multinomial mixed models were used to assess the associations between social vulnerabilities and children's dietary patterns at baseline and follow-up. Children whose parents lacked a social network (OR 1·31; 99 % CI 1·01, 1·70) and migrants (OR 1·45; 99 % CI 1·15, 1·83) were more likely to be in the processed cluster at baseline and follow-up. Children whose parents were homemakers (OR 0·74; 99 % CI 0·60, 0·92) were less likely to be in the processed cluster at baseline. A higher number of vulnerabilities was associated with a higher probability of children being in the processed cluster (OR 1·78; 99 % CI 1·21, 2·62). Therefore, special attention should be paid to children of vulnerable groups as they present unhealthier dietary patterns.